The Ability of Secretory Leukocyte Protease Inhibitor to Inhibit Apoptosis in Monocytes Is Independent of Its Antiprotease Activity - Niamh McGarry; Catherine M. Greene; Noel G. McElvaney; Sinéad Weldon; Clifford C. Taggart (Journal of Immunology Research)
Secretory Leukocyte Protease Inhibitor (SLPI) is a serine protease inhibitor produced by epithelial and myeloid cells with anti-inflammatory properties. Research has shown that SLPI exerts its anti-inflammatory activity by directly binding to NF-κB DNA binding sites and, in so doing, prevents binding and subsequent transcription of proinflammatory gene expression. In the current study, we demonstrate that SLPI can inhibit TNF-α-induced apoptosis in U937 cells and peripheral blood monocytes. Specifically, SLPI inhibits TNF-α-induced caspase-3 activation and DNA degradation associated with apoptosis. We go on to show that this ability of SLPI to inhibit apoptosis is not dependent on its antiprotease activity as antiprotease deficient variants of SLPI can also inhibit TNF-α-induced apoptosis. This reduction in monocyte apoptosis may preserve monocyte function during inflammation resolution and promote infection clearance at mucosal sites.